Doorbell image capturing with notification via SMS and email / Faizal Afiq Mohd Noor - Mohd Noor, Faizal Afiq (2020)
In the present-day, the Internet of things (IoT) has entered a golden era of rapid growth. In the physical world, the Internet of things is an idea that purposes of spreading the advantages of consistent internet constant connectivity, remote control ability, data sharing, and others. Daily jobs are getting linked with the network. This idea can be used to achieve the concerned safety concerns in a rate effective technique. The doorbell system is a method of communication.it usually at the workplace or house. However, the doorbell system has several problems which is a user cannot be heard or alert the sound of the doorbell from source point. Then, the user does not know the identity of the pressed doorbell button. Objectives for this project to design and develop the doorbell image capturing with notification through SMS and Email by applying Raspberry Pi B+, USB Webcam and wireless for achieving the functional requirement that are usability, performance and efficiency. There are many phase connections with this project such as analysis, design, development, implementation and evaluation. In this paperwork, a system is being established to link any door with the internet so that the admission switch system can be organized from anyplace in the creation. In a situation that one is not at home-based and the guest is at the entrance steps, the authorized person is notified of the guest via SMS and the person can see the visitor from the web via the camera from somewhere. And the system takes a visitor's image snap and saves a record by transferring an attachment via e-mail or SMS. The system has been tested using Usability Testing and Functionality Testing. For finding, most people have a problem with the device, such as not heard with long-distance and less awareness. The results from the testing show that the system can solve the current approaches of the doorbell system.